ANALISA EFEK KORONA PADA SISTEM DISTRIBUSI TENAGA LISTRIK 20 KV PADA GARDU BETON - Nurmiati Pasra; Andi Makulau; Muhammad Oka Abriyanto (Sutet, 2018)
The main components of the installation in the Concrete substations are transformers and switching / protection equipment, assembled in civil buildings that are designed, built and functioned by the construction of masonry and concrete pairs. This construction is intended to fulfill the best requirements for electricity safety. The equipment for 20kV medium voltage relations of pair distribution substation is cubicle. PLN's voltage on the one-phase distribution is 11.5kV. with more high feeding stress arises the problem of isolation in the equipment inside the cubicle. The problem that often occurs in cubicles is corona, which is a phenomenon that occurs when air around an conductor or conductor is ionized. From this process there is a discharge that can lead to insulation failure in the air. Based on the influence of the partial pressure of the air on the corona, it can be analyzed the indication of whether or not a corona occurs in the cubicle. From the substation data used, it can be calculated the amount of power losses on the cubicle. From the substation data used, it can be calculated the magnitude of the power losses resulting from fatal distrubtion, because it can cause physical damage to the equipment in the cubicle, causing audio noise and power losses. Substation K-245 has RH = 80%, Ev = 3,94 kV and Ploss = 3,88 kW, then substation K-245 has RH = 86%, Ev = 4,37 kV and Ploss 3,45 kW where the substations T-241 and K-245 are Ev <11,56kV, then the cubicles are exposed to the corona. For substation T-407 has RH = 45%, Ev = 18,34kV, because Ev> 11,56kV then the cubicle is not exposed to the corona.